Facilitators and barriers for the implementation of telemedicine from a local government point of view - a cross-sectional survey in Germany - Maja Maria Weißenfeld; Katja Goetz; Jost Steinhäuser (BMC, 2021)
Abstract Background Telemedicine offers additional ways of delivering medical care, e.g., in primary care in rural areas. During the last decades, projects including telemedicine are being implemented worldwide. However, implementation of telemedicine is in some countries, e.g., Germany somewhat slower compared to northern European countries. One important part of successful implementation is to include the citizen perspective. The aims of this study were to explore the perception of representatives of the local government regarding telemedicine in the context of a perceived GP shortage and to tailor future telemedicine offers according to these perceived needs. Methods Considering the multidisciplinary assessment suggested by the Model for Assessment of Telemedicine a questionnaire with 19 questions was developed by identifying determinants of telemedicine out the literature. After pre-testing, the questionnaire was sent to all 2199 mayors from the federal states of Schleswig-Holstein (North Germany) and Baden-Württemberg (South Germany) as representatives of the citizens (cross- sectional study; full population survey). The final questionnaire contained sections for socio-demographic data, telemedicine and perceived GP shortage. All responses from November 2018 until 2019 were included and analyzed descriptively. Results The response rate was 32% (N = 699), of which 605 were included in the analysis. A majority of the participants stated they live in a rural area and 46% were in the office for up to 8 years. The mayors had predominantly a positive perception about telemedicine (60%) and 76% of them stated, their community would benefit from telemedicine. A GP shortage was reported by 39% of the participants. The highest risk of telemedicine was seen in misdiagnosing. In case of an emergency situation 291 (45%) of the participants considered data privacy as not as relevant. Mayors from a community with a perceived GP shortage had a more negative perception regarding telemedicine. Conclusion The acceptance of telemedicine is rapidly rising compared to former studies. Communities with a perceived GP shortage had a more negative perception. Barriers like data security concerns were seen as less important in case of an emergency. The highest risk of telemedicine was seen in misdiagnosing. These findings need to be considered in designing future telemedicine offers.